2004
DOI: 10.1002/ajh.20098
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thrombosis in patients with malignancy and heparin‐induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is a common immunological drug reaction. After exposure to heparin, some patients develop heparin dependent antibodies with no evidence of thrombosis, while others are at risk of thrombocytopenia, thrombosis, limb loss, and death. We conducted a retrospective chart review on all patients serologically positive for HIT by HPIA ELISA in a single tertiary-care hospital, to determine whether patients with malignancy had an increased risk of thrombotic complications. Medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…40 Other clinical risk factors are concomitant malignancy, female gender, and higher PF4/heparin antibody titer. 41,42 Also, Kelton et al described that the severity of thrombocytopenia predicts a worse prognosis, such as thrombotic progression, amputation, or death. 43 Both arterial and venous thrombosis can occur, with a higher likelihood of occurrence in the localized vascular injury site.…”
Section: Clinical Manifestationmentioning
confidence: 97%
“…40 Other clinical risk factors are concomitant malignancy, female gender, and higher PF4/heparin antibody titer. 41,42 Also, Kelton et al described that the severity of thrombocytopenia predicts a worse prognosis, such as thrombotic progression, amputation, or death. 43 Both arterial and venous thrombosis can occur, with a higher likelihood of occurrence in the localized vascular injury site.…”
Section: Clinical Manifestationmentioning
confidence: 97%
“…The incidence of thrombopenia was identical with the long-term use of LMWH and VKA as assessed in the LITE [28], the CANTHANOX [50] and in the Sideras [64] studies. A retrospective study of patients treated with UFH found 55 episodes of HIT, including 11 in the cancer patients, but did not allow for an estimation of the prevalence of HIT in cancer patients [55]. From two prospectively evaluated groups of 598 patients treated with UFH and 1,754 patients under LMWH, extrapolation of the data estimated a HIT frequency of 1.5% (5/335) in the subgroup of cancer patients [59].…”
Section: The Cost Of Long-term Use Of Lmwh In Cancer Patientsmentioning
confidence: 99%
“…Historically, unfractionated heparin has long been used for VTE prevention in high risk patients. However, because of the burden of monitoring coagulation activity and adverse events such as heparin-induced thrombocytopenia (HIT) [22], sophisticated anticoagulants, such as low molecular heparin (LMWH) or fondaparinux, a pentasaccharide molecule exerting its anticoagulant activity through binding to antithrombin-III, were developed and now are widely used for perioperative thromboprophylaxis throughout the world. Enoxaparin (LMWH) and fondaparinux are now available in Japan.…”
Section: Vte Prophylaxis In Patients Undergoing Cancer Surgerymentioning
confidence: 99%